ROBOTIC CARVING AND ITS PEDAGOGICAL IMPLICATIONS - Garg, Avni; Pooja; Correa, Frederick Sidney; Pradhan, Indira Priyadarsani; Khan, Akhilesh Kumar; Rai, Supriya; Ingale, Kiran (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Robotic carving is fast transforming the modern day activities in the fields of design, engineering, and creative arts by combining computer accuracy with the physical exploration in materials. The technological, educational and pedagogical aspects of robotic carving are discussed in the paper and it is argued that robotic carving is a game changer in the experimental learning. First, it provides a description of the fundamental elements, working principles and software conditions that allow robotic carving systems to work with high fidelity through a variety of materials. It is based on this that the paper will discuss how these systems are being incorporated into curricula in architecture, industrial design and fabrication programs where they reinforce project based learning and interdisciplinary collaboration. Based on constructivist theory and the principles of STEAM education, robotic carving is potentially useful in the development of cognitive and psychomotor skills that are based on the necessity to iterate, prototype, and solve problems in real time. The case studies of universities in the forefront show how robotic fabrication access improves student engagement, creativity, and design agency and provides students with novel assessment modes, which are linked to process, craft, and innovation. The article also takes into account the new opportunities, which are the AI-instigated toolpath generation, adaptable fabrication processes, and ecologically conscious material approaches. Lastly, it outlines the research directions in the future trying to perfect the approaches to curricular integration, broadening the equitable access to fabrication technologies, and concerning ethical aspects of automation in creative fields.